Faktor-Faktor Yang Mempengaruhi Struktur Modal Perusahaan - Solihatul Adawiyah; Tenny Badina; Mohamad Ainun Najib; Ahmad Fatoni (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
This study aims to explain the variables of firm size, profitability, tangibility and non-debt tax shield in influencing the company's capital structure. The research population is Manufacturing Companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2021 period. The data used in this study is panel data from 16 samples of selected companies, with a total sample of 54. The results show that firm size, profitability, tangibility, and non-debt tax shield have a positive and significant effect on the company's capital structure.